FACTORS INFLUENCING THE IMPLEMENTATION OF E-PROCUREMENT WITH PERCEPTIONS OF EASE OF USE AS MEDIATION VARIABLES - Setyadi, Antonius; Prianto, Susilo Edi; Pawirosumarto, Suharno; Ismail, Shafinar (Universitas Brawijaya, Indonesia, 2023)
Cases of corruption that are increasingly rife in the procurement of goods and services have prompted the government to issue a new policy on the use of the e-procurement system. This system is considered capable of overcoming transparency problems so that it is expected to be able to overcome problems in the procurement of goods and services, so that by implementing this system it is necessary to conduct research on the effectiveness of the implementation of the e-procurement system. This research aimed to determine the effect of system and information quality on the successful use of e-procurement at the Universitas Terbuka, with ease of use as a mediating variable. 357 internal users of the e-procurement system made up the population, and 107 people were selected as a sample based on their strata. Additionally, Smart PLS (Partial Least Square) version 4 is the analytical technique employed. The research results show that there is a significant positive influence between system quality and the success of using e-procurement. Moreover, system and information quality had a positive and significant effect on the ease of use. Information quality did not affect the successful use of e-procurement, while system quality had a positive and significant effect through the ease-of-use mediation variable. Information quality also had a positive and significant effect on the successful use of the e-procurement system through the ease-of-use mediation variable.